Workplace Stressors, Employee Welfare, and Productivity - Niere, Marvin Ian E.; Mecon; Narsico, Lalaine O.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was about the delicate balance between employee well-being and organizational productivity. On the one hand, if work demand was too high, employees would be too stressed, and organizational productivity would be affected. On the other hand, if a workplace is too relaxed, the business may not survive. An optimal combination of employee well-being and organizational productivity had to be addressed in equal terms. The method used to identify potential workplace stressors was qualitative in as much as it made use of observations and interviews with informants. The method used to determine levels of workplace stressor experience of employees was descriptive-quantitative. This study made use of employee work stressor experience as leverage to highlight its dynamics with employee welfare and organizational productivity. Work stressors in the context of a fast-food establishment were identified. Employees were given survey questionnaires to determine the levels of workplace stressor experience. One-way ANOVA was used to determine the significance of the difference between workplace stressors, and subsequently, areas of intervention were identified. The conclusions were the following. Role conflict, role ambiguity, work overload, working conditions, and workplace relationships were identified as potential workplace stressors based on fast-food operations and settings. Identified workplace stressors were experienced by employees at varying levels. There was a significant difference between workplace stressors. Interventions were to include all identified stressors beginning with the most prevalent, work overload. Areas of intervention included social and organizational support, employee stress-coping attitudes and skills, work performance abilities, and work-life balance.